DEVELOPMENT OF MILLEALAB VIRTUAL REALITY BASED ON DIGITAL MATHEMATICAL COMMUNICATION SKILLS FOR JUNIOR HIGH SCHOOL STUDENTS - Arfan, Hanan; Amami Pramuditya, Surya; Laelasari (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The development of Millealab Virtual Reality (VR) for teaching algebra in junior high schools has shown promising potential in enhancing digital mathematical communication skills among students. This research aims to create an engaging and interactive learning environment through the use of VR, making algebraic concepts more accessible and comprehensible. The study involved validation tests by subject matter experts and mathematics teachers, revealing that the algebra content presented in VR aligns well with learning objectives. Practical tests across various demographics indicated that VR could significantly increase student interest and understanding of mathematical concepts. However, some students initially struggled to follow VR instructions, requiring proper guidance and support. Despite these challenges, the use of VR in mathematics education demonstrated a high level of student engagement and improved comprehension of algebraic concepts. This suggests the need for ongoing content development, tailored guidance, continuous evaluation, and adjustment of VR- based learning materials to match student capabilities and motivations, ensuring the effective integration of VR technology in mathematics education.